Developing decision support algorithm for hypertension medications for use in a digital therapeutic system - Lee, Jeannie K.; Nicholas, J. Skye; Albadawi, Amani; Insel, Kathleen C. (Frontiers in Drug Safety and Regulation, 2025)
IntroductionAdherence to hypertension medications is low among older people, and there is limited guidance on the safety of taking a missed medication. Knowing the window of time when an older individual can safely take a missed medication could improve adherence and reduce the fear of overdosing. We developed and implemented a decision support algorithm for missed hypertension medications in a digital therapeutic system designed to facilitate self-management of hypertension medications and blood pressure among older adults.MethodsThe medication formulary included hypertension medications and doses available in the United States that are safe for use by older people. The decision support algorithm was developed through a literature review of clinical and pharmacokinetic studies and knowledge of the pharmacology of aging (pharmacokinetics and pharmacodynamics). The algorithm was peer-reviewed and checked against available provider and patient instructions about missed hypertension medications. Case scenarios were used to code the algorithm into the app.ResultsA total of 117 hypertension medications and combination products were included in the formulary of the Medication Education, Decision Support, Reminding, and Monitoring (MEDSReM©) system, a mobile digital therapeutic. The formulary contains medication names and dose options available for selection at onboarding or when medication changes occur. The safe window for taking missed/overdue medication was programmed into the MEDSReM© app for each medication and dosing frequency. The users are presented with “take, snooze, and skip” options when they receive a reminder and open the app to take the medication. If they open the app past the safe window hours, a recommendation to skip that dose and take the next dose at the regular time is presented. If the user decides to take the missed dose, a decision to take or skip the next dose is shown.DiscussionThe MEDSReM© decision support algorithm provides a safe window of time for each hypertension medication for older adults when they need to take their medication after the intended target time has passed. The interdisciplinary collaboration of clinical, technology, and research teams resulted in a novel, older adult-centered, time-specific digital therapeutic intervention to support decision-making about taking missed hypertension medications.